Analysis of Laminated Shells by Murakami’s Zig-Zag Theory and Radial Basis Functions Collocation - D. A. Maturi; A. J. M. Ferreira; A. M. Zenkour; D. S. Mashat (Journal of Applied Mathematics)
The static and free vibration analysis of laminated shells is performed by radial basis functions collocation, according to Murakami’s zig-zag (ZZ) function (MZZF) theory . The MZZF theory accounts for through-the-thickness deformation, by considering a ZZ evolution of the transverse displacement with the thickness coordinate. The equations of motion and the boundary conditions are obtained by Carrera’s Unified Formulation and further interpolated by collocation with radial basis functions.